Efeitos da administração a longo prazo de dietas com diferentes teores de sódio sobre a função renal de ratos hipertensos - Machado, Rebeca Caldeira (2015)
Introduction: High salt intake markedly contributes to hypertension development and its complications, including the chronic kidney disease. However, the molecular mechanisms responsible for renal damages and renal protection produced by high and low salt diets, respectively, are pourly understood. Objective: Investigate the long term effects diets with different sodium chloride content on the kidney function of spontaneously hypertensive rats (SHR) focusing the molecular mechanisms involved in the renal handling of albumin and components of the renal renin angiotensin system (RAS). Methods: Newly weaned (4 weeks) male SHR were fed for 6 months with diets differing only in NaCl content: standard salt diet (NS: 0.3%), low salt diet (LS: 0.03 %), and high salt diet (HS: 3 %). Analysis of renal morphology and function, evaluation of the expression of key molecular components involved in the renal handling of albumin, including proteins of the slit diaphragm (nephrin and podocin) and the endocytic receptor apparatus of proximal tubule (megalin and cubilin) were performed. Furthermore, expression and activity of RAS components (angiotensin converting enzyme -ACE-, ACE2, AT1, AT2 and Mas) were also examined. Results HS produced glomerular hypertrophy and decreased ACE2 and nephrin expressions, loss of morphological integrity of the podocyte processes, and increased proteinuria, characterized by loss of albumine and high molecular weight proteins. Conversely, severe hypertension was attenuated and renal dysfunction was prevented by LS since proteinuria was much lower than in the NS SHRs. This was associated with a decrease in kidney ACE/ACE2 protein and activity ratio and increased cubilin renal expression. Conclusion: Taken together, these results suggest that low sodium intake attenuates hypertension progression in SHRs and preserves renal function. The mechanisms could partially explaining these findings include modulation of the intrarenal ACE/ACE2 balance and the increased cubilin expression. While, high sodium intake worsens hypertensive kidney injury and decreases the expression nephrin.